The ideal substitute for tricuspid valve replacement in patients with congenital heart disease: an unsolved dilemma - Garatti, Andrea; Giamberti, Alessandro; Frigiola, Alessandro; Menicanti, Lorenzo (Translational Pediatrics; Vol 6, No 2 (April 19, 2017): Translational Pediatrics, 2017)
In a recent paper, Burri and colleagues (1) addressed the complex theme of bioprosthesis durability in patients with congenital heart disease (CHD) operated of tricuspid valve replacement (TVR). The authors reviewed a consecutive series of 51 patients (mean age 32 years) affected by CHD (mainly Ebstein disease) operated over a 25 years period of TVR with a bioprosthesis.